2010
DOI: 10.1155/2010/579640
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D Deficiency Cause Hypertension? Current Evidence from Clinical Studies and Potential Mechanisms

Abstract: Vitamin D deficiency is widely prevalent across all ages, races, geographical regions, and socioeconomic strata. In addition to its important role in skeletal development and calcium homeostasis, several recent studies suggest its association with diabetes, hypertension, cardiovascular disease, certain types of malignancy, and immunologic dysfunction. Here, we review the current evidence regarding an association between vitamin D deficiency and hypertension in clinical and epidemiological studies. We also look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 90 publications
2
61
0
4
Order By: Relevance
“…Several workers have reported that Vitamin D also has a role in blood pressure regulation and heart health [1,2]. Rostand [3] observed that cases of high blood pressure increase during winter and in the places that are far away from the equator, both are the situations where a decrease in available sunlight leads to lower Vitamin D production.…”
Section: Introductionmentioning
confidence: 99%
“…Several workers have reported that Vitamin D also has a role in blood pressure regulation and heart health [1,2]. Rostand [3] observed that cases of high blood pressure increase during winter and in the places that are far away from the equator, both are the situations where a decrease in available sunlight leads to lower Vitamin D production.…”
Section: Introductionmentioning
confidence: 99%
“…35 Observational data are compelling, but not adequate for establishing causation. Because interactions between vitamin D, calcium, and parathyroid hormone are complex, separating the effects distinct to vitamin D in clinical trial can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…One similar study showed that people with higher levels of vitamin D had lower blood pressures and a lower risk of developing hypertension [14]. A review in 2013 looked at many studies involving people with hypertension.…”
Section: Association Of Low Vitamin D Levels and Hypertensionmentioning
confidence: 99%